AB0292 Autoantibodies to a novel peptide uh-ra.1 are associated with disease remission in rheumatoid arthritis. (12th June 2018) - De Winter, L.; Vandormael, P.; Stouten, V.; van Steenbergen, H.W.; Geusens, P.; Lenaerts, J.; van der Helm-van Mil, A.H.M.; Verschueren, P.; Somers, V.
Abstract : Background: Autoantibodies have been found in the majority of RA patients and are used clinically as diagnostic and prognostic serum biomarkers. Before truly personalised medicine is available for RA patients, markers that can predict a patient's response to different therapeutic regimens have to be found. In this study, we further characterise autoantibodies to the novel University of Hasselt (UH) peptide UH-RA.1, which have predictive value for an early response to therapy. Antibody reactivity to UH-RA.1 was found in 7%–10% of early RA patients. Presence of anti-UH-RA.1 antibodies in baseline samples from the Leiden Early Arthritis Clinic (EAC) cohort (n=600) appeared to be related to a better outcome as 37% of the antibody-positive group vs 21% of the antibody-negative group reached sustained DMARD-free remission (p=0.016) 1 . Objectives: Our aim is to test the relation between antibody reactivity against UH-RA.1 peptide and early disease remission in baseline RA samples from the CareRA cohort. Methods: Using a custom peptide enzyme-linked immunosorbent assay, the presence of anti-UH-RA.1 antibodies was investigated in the well characterised CareRA cohort 2 . Cut-off for seropositivity was defined by 2 × SD above the mean antibody level of the healthy control group 1 . In the CareRA trial, different treatment regimens consisting of synthetic DMARDs combined with a step down glucocorticoid treatment, were studied. We used 223 baseline RA samples, collected before the start of treatment and early disease remission was defined as a DAS28(CRP) <2.6 at week 16. Results: Antibodies to UH-RA.1 were found in 5% of the baseline samples from the CareRA cohort. Presence of anti-UH-RA.1 antibodies did not seem to be related to early disease remission in the CareRA cohort. Of the antibody positive group, 9/11 (82%) were in remission at week 16, while 152/212 (72%) of the antibody negative group reached early disease remission (p=0.37). However, in UH-RA.1 seropositive patients from the CareRA cohort, antibody levels were found to be significantly higher in baseline samples of patients that reached remission in week 16 (mean rank 120, 51 vs 89, 9, p=0.001). Conclusions: In RA patients, presence of antibodies against UH-RA.1 peptide at baseline is related to sustained DMARD-free remission and high levels of antibodies against UH-RA.1 were correlated with early remission after combination therapy consisting of classical synthetic DMARDs with a step down glucocorticoid treatment. In combination with other predictive markers, antibodies against UH-RA.1 peptide might therefore contribute to an improved early patient stratification and prediction of therapy response. References: [1] De Winter, et al. Rheumatology (Oxford)2016;55(8):1431–6. [2] Verschueren P, et al. Ann Rheum Dis2015;74:27–34. Disclosure of Interest: None declared